Virtual environments in cooperative learning: a contemporary innovative strategy - Pacheco, Lemuel (2021)
Accelerated changes in the educational field due to the Covid-19 crisis helped awaken and strengthen our technological skills. In this sense, the present study, through documentary research, based on an analytical-inductive and deductive method, aims to show the importance of using virtual environments as contemporary innovation. It seeks greater effectiveness in student learning cooperatively and innovatively. The text is structured by explaining how virtual environments contribute favorably to education in the face of the covid-19 crisis and considering the dimension: cooperative learning as a contemporary strategy. The results reveal that teachers and students need to integrate new technological and innovative methodologies for greater learning effectiveness.